2014
DOI: 10.1371/journal.pone.0105195
|View full text |Cite
|
Sign up to set email alerts
|

IL-31 Associated with Coronary Artery Lesion Formation in Kawasaki Disease

Abstract: BackgroundKawasaki disease (KD) is known to be associated with T help (Th) 2 reaction and subsequently allergic diseases. Interleukin-31 (IL-31) has also been reported to be involved in Th2 mediated diseases such as allergic diseases. However, the role of IL-31 in KD has not been previously reported. The aim of this study is to investigate whether IL-31 is associated with KD and its clinical outcome.MaterialA total of 78 KD patients who met the criteria of KD were enrolled in this study as well as 20 age-match… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 30 publications
1
8
0
Order By: Relevance
“…reported that histological findings in KD including vasculitis, endothelial necrosis, and infiltration of mononuclear cells into blood vessels [ 57 ]. In previous studies, plasma levels of inflammatory cytokines (TNF-α, IL-4, IL-5, IL-6, IL-17, IL-31, and IP-10) [ 7 , 8 , 58 62 ], chemokines and adhesion molecules were elevated at the acute stage of KD [ 57 ]. Macrophage colony-stimulating factor (M-CSF) has been performed to play a critical role in the pathogenesis of KD and can be used as an indicator for the risks of valvulitis and coronary arteritis [ 11 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…reported that histological findings in KD including vasculitis, endothelial necrosis, and infiltration of mononuclear cells into blood vessels [ 57 ]. In previous studies, plasma levels of inflammatory cytokines (TNF-α, IL-4, IL-5, IL-6, IL-17, IL-31, and IP-10) [ 7 , 8 , 58 62 ], chemokines and adhesion molecules were elevated at the acute stage of KD [ 57 ]. Macrophage colony-stimulating factor (M-CSF) has been performed to play a critical role in the pathogenesis of KD and can be used as an indicator for the risks of valvulitis and coronary arteritis [ 11 , 63 ].…”
Section: Discussionmentioning
confidence: 99%
“…Intense IL-1β, tumor necrosis factor α and IL-6 are also produced in acute KD patients ( Figure 2 ) ( 22 , 30 , 31 ). IL-31 has also been reported to be involved in Th2-mediated diseases, such as allergic diseases, as well as KD ( 32 ). Eosinophils play an important role in type 2 inflammation ( 33 ).…”
Section: Abnormal Type 2 Inflammation Imbalance T Helper Type 17/regmentioning
confidence: 99%
“…As far as cardiovascular diseases are concerned, the involvement of IL-31 has been studied in Kawasaki's disease. In particular, a study demonstrated how IL-31 expression was related to Kawasaki's disease, and thus, its higher expression could be considered as a promoter of coronary lesions [ 60 ]. On the other hand, serum levels of ST2 in patients affected by heart failure and myocardial infarction were found to be elevated, and the increase of ST2 levels was proposed as a biomarker in forecasting the risk for a cardiac transplantation and the risk of heart failure [ 40 ].…”
Section: Il-31 and Il-33 In Diseasesmentioning
confidence: 99%